Association of seropositivity to Helicobacter species and biliary tract cancer in the ATBC study. Issue 6 (30th July 2014) - Murphy, Gwen; Michel, Angelika; Taylor, Philip R.; Albanes, Demetrius; Weinstein, Stephanie J.; Virtamo, Jarmo; Parisi, Dominick; Snyder, Kirk; Butt, Julia; McGlynn, Katherine A.; Koshiol, Jill; Pawlita, Michael; et al.
<x xml:space="preserve">Abstract</x> Helicobacter have been detected in human bile and hepatobiliary tissue. Despite evidence that Helicobacter species promote gallstone formation and hepatobiliary tumors in laboratory studies, it remains unclear whether Helicobacter species contribute to these cancers in humans. We used a multiplex panel to assess whether seropositivity to 15 Helicobacter pylori proteins was associated with subsequent incidence of hepatobiliary cancers in the Finnish Alpha‐Tocopherol, Beta‐Carotene Cancer Prevention (ATBC) Study. We included 64 biliary cancers, 122 liver cancers, and 224 age‐matched controls which occurred over the course of 22 years. Helicobacter pylori seropositivity was defined as those positive to ≥4 antigens. Odds ratios (OR) and 95% confidence intervals were adjusted for major hepatobiliary cancer risk factors. Among the controls, 88% were seropositive to H. pylori at baseline. Among those who subsequently developed hepatobiliary cancer, the prevalence of seropositivity was higher: 100% for gallbladder cancer, 97% of extrahepatic bile duct cancer, 91% of ampula of Vater cancer, 96% of intrahepatic bile duct cancer, and 94% of hepatocellular carcinoma. Although the OR for gallbladder cancer could not be calculated, the OR for the other sites were 7.01 (95% confidence interval [CI]: 0.79‐62.33), 2.21 (0.19‐25.52), 10.67 (0.76‐150.08), and 1.20 (0.42‐3.45), respectively, with an OR of 5.47 (95% CI: 1.17‐25.65) observed for the biliary tract cancers combined. ORs above 1 were observed for many of the investigated antigens, although most of these associations were not statistically significant. Conclusion: Seropositivity to H. pylori proteins was associated with an increased risk of biliary tract cancers in ATBC. Further studies are needed to confirm our findings and to determine how H. pylori might influence the risk of biliary tract cancer. (Hepatology 2014;60:1962–1970)